SPATIAL CO-MANAGEMENT OF INDONESIAN FLOODPLAIN RIVER FISHERIES - Daniel D. Hoggarth; Mark A. Thomas; Achmad S. Sarnita; Ondara Ondara (Indonesian Fisheries Research Journal, 1998)
An interdisciplinary investigation was nrade on the mechanisms underlying the development of local manugement systems for floodplain river fisheries in Sumatera